Principal Management and Educational Transformation under the Independent Curriculum - Yeni Suntari; Silvia Purwaningsih (BRIDGE : The Multidisciplinary Research Portal, 2024)
This study explores the role of principal managerial ability in the successful implementation of the Independent Curriculum (Kurikulum Merdeka) at SMAN 2 Kotaagung, Indonesia. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis involving principals, teachers, students, and parents. The findings reveal that the principal’s proactive leadership characterized by structured professional development, continuous mentoring, and inclusive decision-making plays a pivotal role in facilitating curriculum adaptation and fostering an innovative school culture. Teacher engagement, enabled by ongoing support and reflective practices, contributes to effective pedagogical transformation, while students experience heightened engagement, motivation, and learning outcomes. The active involvement of parents and community stakeholders, together with a robust monitoring and evaluation framework, ensures that curriculum implementation remains responsive and sustainable. This research highlights that collaborative leadership, continuous professional growth, and stakeholder participation are key drivers for successful educational transformation in the context of curriculum reform. The implications of these findings are relevant for policymakers, school leaders, and educators aiming to advance holistic and adaptive educational change.